Nursing science development for nursing practice: a philosophical perspective - Manee Arpanantikul; Amar Akbar (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2018)
Knowledge development , research methodology definitely related to the philosopher's framework, it was very important for a scientific discipline to realize the philosophical orientation that is the basis for the development of theory and advancing science in nursing. Science becomes knowledge with the publication of results, then continue to grow as general knowledge and continued by wrote in text books, this ways would makes history to correct errors, science used physical evidence to answer questions and depends on modern humans to draw conclusions from the evidence, science looks to explain original sources, nature, and physical processes that might be detected in the univers. In practicing nursing science, nurse should stand in professional character as way to compete with others profession with several ways : 1) Legitimate job to brew great denomination 2) Valid proof in specific practice area 3) Diverse nursing knowledge in practice and theory 4) Control and standard in strong educational arrangement 5) Set up official organization in practice and education 6) Define interpersonal side in part of profession 7) Outrageously expand for ethical code and action